MiR-101 Is Involved in Human Breast Carcinogenesis by Targeting Stathmin1 - Wang, Rui; Wang, Hong-Bin; Hao, Chan Juan; Cui, Yi; Han, Xiao-Chen; Hu, Yi; Li, Fei-Feng; Xia, Hong-Fei; Ma, Xu (PLOS ONE, 2012)
Background MicroRNA-101 (miR-101) expression is negatively associated with tumor growth and blood vessel formation in several solid epithelial cancers. However, the role of miR-101 in human breast cancer remains elusive. Results MiR-101 was significantly decreased in different subtypes of human breast cancer tissues compared with that in adjacent normal breast tissues (P<0.01). Up-regulation of miR-101 inhibited cell proliferation, migration and invasion, and promoted cell apoptosis in ER alpha-positive and ER alpha-negative breast cancer cells and normal breast cells. Down-regulation of miR-101 displayed opposite effects on cell growth and metastasis. Further investigation revealed a significant inverse correlation between the expression of miR-101 and Stathmin1 (Stmn1), and miR-101 could bind to the 3′-untranslated region (UTR) of Stmn1 to inhibit Stmn1 translation. The inhibition of cell growth and metastasis induced by up-regulation of miR-101 was partially restored by overexpresson of Stmn1. Knockdown of Stmn1 attenuates the down-regulation of miR-101-mediated enhancement of cell growth and metastasis. More importantly, in vivo analysis found that Stmn1 mRNA and protein level in different subtypes of human breast cancer tissues, contrary to the down-regulation of miR-101, were significantly elevated. Conclusions This study demonstrates that down-regulation of miR-101 in different subtypes of human breast cancer tissues is linked to the increase of cellular proliferation and invasiveness via targeting Stmn1, which highlights novel regulatory mechanism in breast cancer and may provide valuable clues for the future clinical diagnosis of breast cancer.